Heterogeneity of osteoclast activity and bone turnover in different skeletal sites. (November 2016) - Goldberg, S.; Grynpas, M.D.; Glogauer, M.
Highlights: Osteoclast activity and bone turnover in different skeletal sites. In vitro resorption pit confocal method to measure volume and surface area. TRAP, static and dynamic histomorphometry to measure in vivo bone turnover. Abstract: Objective: To compare osteoclasts and bone turnover in the cranial and appendicular skeletons of mice and determine whether estrogen depletion has an impact on these differences. Design: In vitro osteoclastogenesis (OCG) was performed on osteoclasts precursors derived from calvarial, mandibular and femoral bone marrow. In vitro, mature osteoclasts were stained with TRAP in plastic petri dishes and with DAPI and Phalloidin on glass coverslips to identify mature osteoclasts and compare osteoclast surface area and nuclei number in the different bone sites, respectively. Quantification of osteoclast resorption pit (Rpit) volume and surface area from different bone sites was achieved using dentin slices stained with Picrosirius red and confocal microscopy. In vivo TRAP, static and dynamic histomorphometric analyses were performed on 5-month-old mouse calvarial, long bone and mandibular trabecular bone to compare bone resorption and formation rates, respectively. Mice were ovariectomized (OVX) at 5 months of age and sacrificed at 6 months of age to establish an osteoporosis model for differences in osteoclasts activity and to monitor the changes in bone turnover rates in the three bone sites upon estrogen depletion. Result: s Phalloidin stained calvarial osteoclasts were larger compared to long bone and mandibular osteoclasts. Rpits from osteoclasts derived from mandibular bone were smaller and had lower volume values compared to long bone and calvarial bone Rpits. In vivo analysis showed significant increases in bone formation rates in calvarial trabecular bone compared to long bone and mandibular trabecular bone. Turnover was enhanced upon estrogen depletion in calvarial trabecular bone. Resorption was increased without a corresponding increase in bone formation in the trabecular metaphysis of long bone. Mandibular trabecular bones do not appear to be affected by OVX. Conclusion: The cranial and appendicular skeletons differ from one another in that osteoclasts from calvarial bone have the highest resorptive capacity which is coupled to bone formation both pre and post-OVX. Mandibular bones show the lowest turnover rates and are not affected by OVX.